2008
DOI: 10.1002/asna.200710972
|View full text |Cite
|
Sign up to set email alerts
|

Possible third body effects in the period changes of four Algol binaries: RY Aqr, SZ Her, RV Lyr and V913 Oph

Abstract: An investigation of the orbital period changes of the neglected eclipsing binaries, RY Aqr, SZ Her, RV Lyr and V913 Oph, is presented based on all published minima times. Although the explanation of magnetic activity on the surface of the secondaries of the studied Algols is still open, the preferred light-time effect due to the unseen components around the systems seems more plausible in explaining the tilted sinusoidal variations with relatively high-amplitudes. The minimal mass values of possible tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Previous researchers (Székely 2003;Soydugan 2008) have suggested that the period variations of SZ Her can be represented using an LITE caused by the presence of a third body in the system.…”
Section: Orbital Period Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researchers (Székely 2003;Soydugan 2008) have suggested that the period variations of SZ Her can be represented using an LITE caused by the presence of a third body in the system.…”
Section: Orbital Period Studymentioning
confidence: 99%
“…They reported that the period change can be described using either a sine curve or a single light-time effect (LITE) ephemeris due to a third body with implied periods of 66 and 71 yr, respectively. Soydugan (2008) also suggested that the timing residuals from the LITE fit indicate an additional short-term oscillation with a period within about 20 yr. More than one thousand eclipse timings, spanning ∼ 110 yr, should be sufficient to resolve the confusion regarding the orbital behavior of SZ Her. Nonetheless, the period variation of this system has not yet been studied as conclusively as required.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The former reported that the period change can be fitted to a sine curve with a period of 66 yr, while the latter concluded that it can be represented by a single light-time-travel (LTT) ephemeris, caused mainly by a third body with a cycle length of 72 yr and a minimum mass of 0.25 M . Soydugan (2008) also suggested that the timing residuals from the LTT fit indicate an additional short-term oscillation with a period within about 20 yr. Nonetheless, the period variation still has not been studied as conclusively as can be desired.…”
Section: Introductionmentioning
confidence: 99%
“…Although the orbital period of SZ Her has been examined several times, its detailed study was made by Szekely (2003) and Soydugan (2008). The former reported that the period change can be fitted to a sine curve with a period of 66 yr, while the latter concluded that it can be represented by a single light-time-travel (LTT) ephemeris, caused mainly by a third body with a cycle length of 72 yr and a minimum mass of 0.25 M .…”
Section: Introductionmentioning
confidence: 99%